The freak-garde : extraordinary bodies and revolutionary art in America - Blyn, Robin (University of Minnesota Press, 2013)
"Since the 1890s, American artists have employed the arts of the freak show to envision radically different ways of being. The result is a rich avant-garde tradition that critiques and challenges capitalism from within. The Freak-garde traces the arts of the freak show from P.T. Barnum to Matthew Barney and demonstrates how a form of mass culture entertainment became the basis for a distinctly American avant-garde tradition. Exploring a wide range of writers, filmmakers, photographers, and artists who have appropriated the arts of the freak show, Robin Blyn exposes the disturbing power of human curiosities and the desires they unleash. Through a series of incisive and often startling readings, Blyn reveals how such figures as Mark Twain, Djuna Barnes, Tod Browning, Lon Chaney, Nathanael West, and Diane Arbus use these desires to propose alternatives to the autonomous and repressed subject of liberal capitalism. Blyn explains how, rather than grounding revolutionary subjectivities in imaginary realms innocent of capitalism, freak-garde works manufacture new subjectivities by exploiting potentials inherent to capitalism itself. Defying conventional wisdom, The Freak-garde ultimately argues that postmodernism is not the death of the avant-garde but the inheritor of a vital and generative legacy. In doing so, the book establishes innovative approaches to American avant-garde practices and embodiment and lays the foundation for a more nuanced understanding of the disruptive potential of art under capitalism."--